Beispiel Nr: 16
$ \text{Gegeben:} \\ a1 \cdot x + b1\cdot y + c1\cdot z=d1\\ a2\cdot x + b2\cdot y + c2\cdot z=d2\\ a3\cdot x + b3\cdot y + c3\cdot z=d3\\ \\ \text{Gesucht:} \\\text{x,y,z} \\ \\ \textbf{Gegeben:} \\ 6 x +4 + 5 z=8\\ 4 x +2 y + 3 z=7\\ 5 x +3 y + 4 z=9\\ \\ \\ \textbf{Rechnung:} \\\small \begin{array}{l} 6x+4y+5z=8 \\ 4x+2y+3z=7 \\ 5x+3y+4z=9 \\ \\ \end{array} \qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline6 & 4 & 5 & 8 \\ 4 & 2 & 3 & 7 \\ 5 & 3 & 4 & 9 \\ \end{array} \\ \\ \begin{array}{l}\text{Zeile}2=\text{Zeile}2\cdot 6\text{-Zeile}1\cdot 4 \\z2s1=4\cdot 6-6\cdot 4 =0 \\ z2s2=2\cdot 6-4\cdot 4 =-4 \\ z2s3=3\cdot 6-5\cdot 4 =-2 \\ z2s4=7\cdot 6-8\cdot 4 =10 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline6 & 4 & 5 & 8 \\ 0 & -4 & -2 & 10 \\ 5 & 3 & 4 & 9 \\ \end{array} \\ \\ \begin{array}{l}\text{Zeile}3=\text{Zeile}3\cdot 6\text{-Zeile}1\cdot 5 \\z3s1=5\cdot 6-6\cdot 5 =0 \\ z3s2=3\cdot 6-4\cdot 5 =-2 \\ z3s3=4\cdot 6-5\cdot 5 =-1 \\ z3s4=9\cdot 6-8\cdot 5 =14 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline6 & 4 & 5 & 8 \\ 0 & -4 & -2 & 10 \\ 0 & -2 & -1 & 14 \\ \end{array} \\ \\ \begin{array}{l}\text{Zeile}3=\text{Zeile}3\cdot (-4)\text{-Zeile}2\cdot (-2) \\z3s2=(-2)\cdot -4-(-4)\cdot (-2) =0 \\ z3s3=(-1)\cdot -4-(-2)\cdot (-2) =0 \\ z3s4=14\cdot -4-10\cdot (-2) =-36 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline6 & 4 & 5 & 8 \\ 0 & -4 & -2 & 10 \\ 0 & 0 & 0 & -36 \\ \end{array} \\ \\ \\ L=\{\}$